Study of the most responsible parameters on polarization for powerful preliminary test of oil quality - Ketut Sofjan Firdausi; Suryono Suryono; Priyono Priyono; Zaenul Muhlisin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
In this study, the most responsible parameters on polarization in total natural vegetable oils and fats have been investigated by determination of the relation between the polarization change and fatty acids (FA) composition. The change of light polarization was simply measured by using a pair of polarizer-analyser to indicate oil quality level, and the FA composition was obtained by using Gas Chromatography and Mass Spectrometer (GCMS) method. Various vegetable oils and fats were examined without any preliminary treatments. The experimental condition of the samples during measurement was assumed to be constant. It has been shown that various oils and fats have different angle of change of polarization, which indicates various oil quality level relative to each other, in agreement to the previous works. Especially for vegetable oils, high change of polarization has been considered as low quality of oil. The long chain of saturated fatty acids (SFA) and unsaturated fatty acids (UFA), which are distributed at third position (R3) and first position (R1) of triglycerides (TG) molecules, are responsible for the change of polarization and presented as a linear combination of the number of SFA or UFA. The result shows that the polarization could be used as powerful method for preliminary detection of oil quality level. The highest number of coefficient of C19:0 in lard indicates that this method has provided good prospect to evaluate the halal level of oil due to lard contamination.Keywords—polarization, triglyceride (TG), saturated fatty acid (SFA), unsaturated fatty acids (UFA)